2022
DOI: 10.1002/acr.24833
|View full text |Cite
|
Sign up to set email alerts
|

Depressed Symptomatology in Systemic Lupus Erythematosus Patients

Abstract: Objective. Depression is a prevalent (24-30%) and significant comorbidity in patients with systemic lupus erythematosus (SLE). In the present study, we leveraged the longitudinal SLE cohort at the Washington University Lupus Clinic to address 1) what is the longitudinal course of depressed affect among outpatients with SLE and 2) what is the longitudinal relationship between SLE disease activity and depressed affect?Methods. Longitudinal data from patients with American College of Rheumatology-or Systemic Lupu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…Patients' depression severity was also found to be consistently associated with anxiety symptoms over time. We previously reported that severity of depressed affect can also be classified into distinct trajectory groups that were similarly durable over time ( 18 ). When we examined baseline depression scores across the four anxiety trajectory groups, a dose–response relationship was observed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients' depression severity was also found to be consistently associated with anxiety symptoms over time. We previously reported that severity of depressed affect can also be classified into distinct trajectory groups that were similarly durable over time ( 18 ). When we examined baseline depression scores across the four anxiety trajectory groups, a dose–response relationship was observed.…”
Section: Discussionmentioning
confidence: 99%
“…With these considerations in mind, we recently reported that depressed affect is both persistent and largely severe for up to 4 years in a Washington University cohort of patients with SLE ( 18 ). We were further curious to determine whether similar findings may be present for anxiety in this cohort.…”
Section: Introductionmentioning
confidence: 99%
“…Our results are in agreement with a longitudinal study of 139 SLE patients which revealed four distinct anxiety trajectories that remained stable and not affected by disease activity over an average period of 30.9 months [ 58 ]. A similar analysis focusing on depression also showed persistence over time and a lack of association with temporal trends in SLEDAI-2K (average follow-up of 30.2 months) [ 59 ]. Collectively, and in line with a previous cohort study indicating that depression might be a long-term outcome of SLE [ 54 ], these data suggest that fluctuations of disease activity might not be major drivers of anxiety and depression, especially in the context of long-standing disease, although it has been argued that prolonged remission (i.e., lasting at least 5 years) might have a positive impact on depression [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…The most extended observation period for mood disorders in SLE was 48 months, and this study’s results emphasize that the level of SLE disease activity was associated with depression scores in the multivariate analysis. Still, no significant association was evident in the univariate analysis [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…This study also highlighted that SLE activity was not longitudinally linked to anxiety when managing depression and other factors [ 18 ]. Another study on the longitudinal progression of depression, covering a similar four-year period, found that a significant portion (61.2%) of patients exhibited consistent symptoms of depression or major depressive disorder as per the Center for Epidemiologic Studies Depression Scale—Revised (CESD-R) scores [ 19 ]. Since anxiety and depression seem to be the most encountered psychiatric manifestations of NPSLE [ 20 ], the study presented in this paper aimed to investigate the progression of anxiety and depression in patients with NPSLE over a year.…”
Section: Introductionmentioning
confidence: 99%